The Social and Political Implications of Demographic Change in Post-Apartheid South Africa. Issue 1 (March 2014) - Seekings, Jeremy
The cohort of young people born between the early 1980s and early 1990s consitute a demographic bulge in the South African population. The sheer size of this cohort renders it especially important in terms of the changing political, economic, and social life of the country. The cohort grew up for the most part after apartheid had ended, entered the labor market at a time of high unemployment, is having children as marriage is in decline, and reached voting age just as the African National Congress's (ANC's) moral stature began to decline. All these factors might be expected to result in distinctive disaffection and a propensity for dissent. In terms of their attitudes and behavior, however, this cohort looks much like older (or immediately preceding) cohorts of South Africans. Where this cohort is likely to leave its mark is in entrenching some of the social, economic, and political changes that, until recently, might have appeared transient.